Gender Inequality And Women Empowerment In Warri South Local Government Area Of Delta State, Nigeria - Aniah, Evaristis Akomaye, Uyang, Francis Abul Ejeje, Joy Aboli (Social Science Learning Education Journal, 2016)
The study investigates gender inequality and women empowerment in Warri South Local Government Area of Delta State, Nigeria. Two null hypotheses were formulated guided by the independent variable gender inequality (in access to educational services and participation in governance) women empowerment. Using the survey research design, data were statistically analyzed using the chi-square (X2) with significance level at 0.05. The results showed that a significant relationship exists between access to educational services and women empowerment; also, a positive relationship exists between participation in governance and women empowerment. The study recommends, among others, that women should be allowed to engage in equal economic activities like their made counterpart outside their home in other to reduce dependency and poverty rate among them.Â  Also women should be allowed in making decisions that affect them. It was concluded that gender inequality is a significant source of women disempowerment.